Calcium and Cholecalciferol Levels in Late-Phase Laying Hens: Effects on Productive Traits, Egg Quality, Blood Biochemistry, and Immune Responses - Attia, Youssef A.; Al-Harthi, Mohammed A.; Abo El-Maaty, Hayam M. (Frontiers in Veterinary Science, 2020)
Productive traits and immunity in laying hens decrease sharply during the late phase of laying due to aging, which negatively affects the metabolism and hormonal status of the animals. The influence of Ca levels (3.5, 4.0, and 4.5%) and/or cholecalciferol [Vitamin D3 (VD3)] supplementation (800-, 1,000-, and 1,200-IU/kg diet or as total of 3,800, 4,000, and 4,200 IC VD3) on performance, egg quality, blood biochemistry, and immunity of brown egg layers was investigated. Three hundred and sixty H&N Brown egg layers (60 weeks old) were allocated at random into nine nutritional treatments of five replications (cages) of eight hens each. The control diet in this experiment contained a 3.5% Ca level with 800 IU VD3. The addition of VD3 at 1,000 and 1,200 IU to 3.5 and 4% Ca diets significantly (P ≤ 0.05) increased the rate of laying, egg mass, and feed conversion ratio (FCR) compared to the control diet on 3.5% and 800 U of VD3. Besides this, the addition of VD3 at 800 and 1,200 IU to 3.5% Ca level diets enhanced the Haugh unit score. Similar results were observed in eggshell quality measurements and tibia ash. Increasing the Ca concentration from 3.5 to 4 and 4.5% and increasing VD3 levels from 800 to 1,000 or 1,200 IU significantly and similarly increased serum total protein and globulin. In addition, VD3 at 1,000 IU increased serum albumin, compared to 800 IU. Increasing Ca level increased IgA, and 4 and 4.5% Ca levels similarly increased IgG and α-2 globulin compared to the 3.5% Ca diet. VD3 addition at 1,200 IU to the 4% Ca diet significantly increased γ-globulin compared to 1,000 IU, but decreased β-globulin. Increasing the Ca level to 4% significantly reduced serum triglycerides, and the very low-density lipoprotein and the triglyceride/high-density lipoprotein ratio were both decreased with 4 and 4.5% Ca level diets. Increasing the Ca level caused a stepwise increase in catalase, which was markedly increased with VD3 supplementation at 1,200 IU. Plasma estrogen was increased considerably with VD3 supplementation at 3.5% Ca, but parathyroid hormone levels were not affected. In conclusion, increasing Ca levels in the diet of laying hens to 4% during the late production phase could be a useful tool to improve laying performance, eggshell quality, Haugh unit score, and physiological and immunological status. Besides, VD3 at a 1,000 IU/kg diet to 3.5% Ca improved performance of hens fed 3.5% Ca, showing that the potential impact of VD3 depends on Ca concentrations.